ALS and Frontotemporal Dysfunction: A Review - Eugene Y. Achi; Stacy A. Rudnicki (Neurology Research International)
Though once believed to be a disease that was limited to the motor system, it is now apparent that amyotrophic lateral sclerosis (ALS) may be associated with cognitive changes in some patients. Changes are consistent with frontotemporal dysfunction, and may range from mild abnormalities only recognized with formal neuropsychological testing, to profound frontotemporal dementia (FTD). Executive function, behavior, and language are the most likely areas to be involved. Screening helpful in detecting abnormalities includes verbal or categorical fluency, behavioral inventories filled out by the caregiver, and evaluation for the presence of depression and pseudobulbar affect. Patients with cognitive dysfunction have shortened survival and may be less compliant with recommendations regarding use of feeding tubes and noninvasive ventilation. Evolving knowledge of genetic and pathological links between ALS and FTD has allowed us to better understand the overlapping spectrum of ALS and FTD.